Agree to disagree: in the context of on going global religious conflicts - U Tun Aung, Maulana Akbar Shah (2015)
Since the number of unsolvable problems with regards to peace and security faced by human beings on our sphere has been greater than what they can bear, survival of human race seriously solicits a resolution by ovecoming whatever difficulties standing in their way. Despite growing scienctific development, latest sophisticated arms, communitive apparatus and the best medical facilities, mankind encounters more complicated and unhealthy issues. Albeit many experts seemed difficult in trying to find out its solution through unpopular research and expensive exploration, the answer to the said problem according to the researcher is not so difficult. The Only thing that one should know to find out the solution is the connection between man and his rights. As long as their rights and needs are fullfiled, no disagreement or dispute can ever be erupted in a society. However, today’s problems in our globe are caused, for rights are not properely provided to the right people when the responsibilities are not duely conducted according to their norms. As a result, the louder claims from different communities belonging to particularly ethnical and religious environments are the hits of our media and network. The majority of the problems we are facing is influenced by the problems of religious disputes, ethnical tensions and sectarion violences.